EXOTIZACIÓN, DOMESTICACIÓN Y NIVELACIÓN EN LA TRADUCCIÓN DE OBRAS LITERARIAS Y DE TÍTULOS DE OBRAS DE ARTE PLÁSTICO - José Manuel POZO LÓPEZ (Diversitate si Identitate Culturala in Europa)
The theory of literary translation presupposes, apart from the norms that requi re a minimum semantic equivalence between the source language and the target language, a strategy of the translator's intervention in the text as well. This strategy is oriented towards three directions, as follows: 1) the translator replaces linguistic an d cultural elements specific to the original text with elemen ts that are characteristic to the culture it addresses, in order to facilitate a better understanding for the readers; 2) the translator preserves those three elements specific to the “exotic app earance” that confer upon the text its uniqueness dimension; 3) the translator brings together, through “cultural levelling” (which is intimately related to the adequacy of the first direction), conceptual and stylistic elements intrinsic to the source tex t and elements that are intrinsic to the target language. As the relationship between form and content constitutes the essence of artistry itself, the translator will endeavour to make his efforts head for an act of creation and not of betrayal towards the original text.